2019
DOI: 10.1093/cid/ciz1181
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Esophageal Varices by Liver Stiffness and Platelets in Persons With Human Immunodeficiency Virus Infection and Compensated Advanced Chronic Liver Disease

Abstract: Background People living with human immunodeficiency virus (PLWH) are at increased risk of cirrhosis and esophageal varices. Baveno VI criteria, based on liver stiffness measurement (LSM) and platelet count, have been proposed to avoid unnecessary esophagogastroduodenoscopy (EGD) screening for esophageal varices needing treatment (EVNT). This approach has not been validated in PLWH. Methods PLWH from 8 prospective cohorts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…17 This led to an expert recommendation to use these non-invasive criteria (defined "Baveno VI" criteria) to spare endoscopy in patients with cACLD. Since the publication of the criteria, several studies and 2 meta-analyses 280,281 confirmed the validity of this approach in all the major aetiologies of liver disease including HIV-HCV coinfection 282 and patients who achieved SVR after treatment of HCV, 283 showing rates of missed high-risk varices ranging from 0 to 2%; hence, these criteria can be considered validated. Since the Baveno VI criteria are conservative and enable no more than 10-25% of endoscopies to be spared, studies looking for expanded criteria have been published.…”
Section: Recommendationsmentioning
confidence: 95%
“…17 This led to an expert recommendation to use these non-invasive criteria (defined "Baveno VI" criteria) to spare endoscopy in patients with cACLD. Since the publication of the criteria, several studies and 2 meta-analyses 280,281 confirmed the validity of this approach in all the major aetiologies of liver disease including HIV-HCV coinfection 282 and patients who achieved SVR after treatment of HCV, 283 showing rates of missed high-risk varices ranging from 0 to 2%; hence, these criteria can be considered validated. Since the Baveno VI criteria are conservative and enable no more than 10-25% of endoscopies to be spared, studies looking for expanded criteria have been published.…”
Section: Recommendationsmentioning
confidence: 95%
“…The use of dual cut-offs may overcome both these limitations and introduce uniformity in the diagnosis of chronic liver disease. The Baveno VI criteria on screening for varices needing treatment including LS values <20 kPa and platelet count >150×10 9 cells/L(1) have already been validated in several small to medium independent J o u r n a l P r e -p r o o f cohorts (7)(8)(9)(10) and in a recent large meta-analysis of 30 studies (11). However, the criteria to rule in and out cACLD have not been externally validated in a real-world population until now.…”
Section: Introductionmentioning
confidence: 99%
“…Certain antiretroviral therapies, particularly didanosine, have been associated with non-cirrhotic portal hypertension [6]. Once ACLD and portal hypertension develop, PWH are at risk of variceal bleeding, ascites, hepatic encephalopathy and early death [4,7,8]. A finding of splenomegaly on ultrasound, a readily available tool in the practice of HIV medicine, does not suffice to refer for portal pressure measurements or endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…A finding of splenomegaly on ultrasound, a readily available tool in the practice of HIV medicine, does not suffice to refer for portal pressure measurements or endoscopy. Liver stiffness measurement (LSM) by transient elastography (TE) has allowed the noninvasive assessment of ACLD and identification of PWH with portal hypertension at risk for liver-related events [4,7,8]. However, TE is not a test routinely performed in PWH in clinical practice.…”
Section: Introductionmentioning
confidence: 99%